Sistem Informasi Penerimaan Karyawan Berbasis Website Pada PT Federal International Finance Cabang Kota Tegal - Wati, Fanny Fatma; Widodo, Andrian Eko; Abror, Dzulchan (J-INTECH (Journal of Information and Technology), 2024)
Human Resources (HR) is indeed very influential for the success of an organization, and an effective selection process is one of the keys to ensure that the selected human resources have motivation, ability in the company. By conducting a good selection process, companies can ensure that they get the right individuals for the available positions. Changing the selection process from a manual method to an online system through the official website will bring many advantages. These include increased efficiency in managing applicant data, expanding the range of candidate searches, and speeding up the selection process. At PT Federal Internasional Finance in the employee recruitment process still uses a manual system so a website is needed to facilitate the employee recruitment process to be more effective and efficient. In making this website using the waterfall method starting from the planning stage to the system maintenance stage. The results of this study are computerized acceptance of new employees, expected to be able to contribute to the company, especially Human Resources (HR). The process of accepting prospective new employees of PT. Federal International finance spends a long time, will have a direct impact on inefficient data which will cause inaccuracies in a data.